TESTING THE EFFECTIVENESS OF VEGETABLE PESTICIDES AND GOAT URINE POC FOR PEST PREVENTION AND GROWTH OF ONION (Allium ascolanicum L.) - Aezad, M. Hafiq; Ginting, Tri Yaninta; Hakim, Tharmizi (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
The excessive use of pesticides and synthetic fertilizers will result in a decrease in nutrients resulting in an impact on shallot productivity, so that shallot production in Indonesia still does not meet consumer demand. This study aims to determine the effect of dosing of vegetable pesticides and POC of goat urine on shallots. This study used a factorial Group Random Design (RAK), with 3 replicates. The first factor is the use of vegetable pesticides from mahogany seeds with 3 concentration levels, namely M0 = 0 ml/100 ml of water/plot, M1 = 30 ml/100 ml of water/plot, and M2 = 60 ml/100 ml of water/plot. The second factor is liquid organic fertilizer from goat urine with 3 concentration levels, namely K0 = 0 ml/liter of water/plot, K1 = 200 ml/liter of water/plot, and K2 = 400 ml/liter of water/plot. The variables observed were plant height, wet weight, dry weight, attack intensity, and arthropod diversity. The results of the study were taken at the age of 2,3,4,5, and 6 weeks after planting (MST). The treatment of vegetable pesticides and POC of goat urine did not produce an interaction on the observed variables of plant height, wet weight, and dry weight. The results showed that the treatment of vegetable pesticides with the highest concentration at M2 resulted in a plant height of 32.60 cm, a wet weight of 35.14 grams and a dry weight of 27.11 grams. Meanwhile, the treatment of goat urine liquid organic fertilizer was the highest, resulting in a plant height of 32.73 cm in the K2 treatment. For wet weight, and dry weight, the highest treatment was in K1 with a wet weight yield of 36.92 grams, and dry weight of 29.14 grams. Regarding the intensity of pest attacks, the results of the study showed that in the first week no attacks were found. However, in weeks 2 to 6 attacks began to appear, with the highest intensity of 0.19 in the M0 treatment. The analysis of Arthropod diversity showed an index of 1.8. which indicates the level of species diversity that is currently in the research field. Overall, this study shows an increase in the growth and production of shallot plants.